MEMBANGUN BUDAYA TOLERANSI DI SEKOLAH MELALUI PENDEKATAN SOCIAL PEDAGOGY: ANALISIS LITERATUR REVIEW - Sutarti, Titin (Widya Aksara : Jurnal Agama Hindu, 2025)
This research aims to analyze how the Social Pedagogy approach can be used in building a culture of tolerance in schools. Social Pedagogy as an educational approach emphasizes the importance of social interaction as well as the development of social and emotional skills to create an inclusive environment. This research uses a qualitative method with a literature review approach. The analysis was conducted using the content analysis method, which includes identifying the main concepts, categorizing the data, synthesizing the results of previous research, and drawing conclusions. The results show that the implementation of Social Pedagogy in schools can strengthen tolerance values through a social experience-based curriculum, collaborative learning, and the role of teachers as facilitators who guide students in understanding diversity. This approach also proved effective in building students' social awareness and improving cross-cultural communication skills. With support from various parties, including educators, parents, and inclusive education policies, Social Pedagogy can be an effective strategy in shaping a generation that is more open, empathetic, and respectful of differences.